2015
DOI: 10.3389/fpsyg.2015.01570
|View full text |Cite
|
Sign up to set email alerts
|

Emotion recognition through static faces and moving bodies: a comparison between typically developed adults and individuals with high level of autistic traits

Abstract: We investigated whether the type of stimulus (pictures of static faces vs. body motion) contributes differently to the recognition of emotions. The performance (accuracy and response times) of 25 Low Autistic Traits (LAT group) young adults (21 males) and 20 young adults (16 males) with either High Autistic Traits or with High Functioning Autism Spectrum Disorder (HAT group) was compared in the recognition of four emotions (Happiness, Anger, Fear, and Sadness) either shown in static faces or conveyed by moving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 86 publications
(121 reference statements)
7
29
0
Order By: Relevance
“…Deficient BM processing has been reported in a wide range of neuropsychiatric diseases including ASD (Klin et al, ; Koldewin et al, ; Nackaerts et al, ; Alaerts et al, ; Cleary et al, ; Kröger et al, ; for review see Pavlova, ), schizophrenia (Kim et al, ; van den Stock et al, ; Hasting et al, ; Spencer et al, ; Hashimoto et al, 2016; Vaskinn et al, ), schizotypal personality disorder (Hur et al, ), ADHD (Kröger et al, ), anxiety disorders (van de Cruys et al, ; Heenan and Troje, ), obsessive compulsive disorders (Kim et al, ). BM processing is also impaired in individuals with autistic traits (Actis‐Grosso et al, ), and in individuals born preterm who suffer congenital brain lesions (Pavlova et al, ; Taylor et al, ; for review see Pavlova and Krägeloh‐Mann, ). Individuals with ASD have also been reported to be impaired on facial BM processing (O'Brien et al, ).…”
Section: Body Motion and Body Language Readingmentioning
confidence: 99%
See 1 more Smart Citation
“…Deficient BM processing has been reported in a wide range of neuropsychiatric diseases including ASD (Klin et al, ; Koldewin et al, ; Nackaerts et al, ; Alaerts et al, ; Cleary et al, ; Kröger et al, ; for review see Pavlova, ), schizophrenia (Kim et al, ; van den Stock et al, ; Hasting et al, ; Spencer et al, ; Hashimoto et al, 2016; Vaskinn et al, ), schizotypal personality disorder (Hur et al, ), ADHD (Kröger et al, ), anxiety disorders (van de Cruys et al, ; Heenan and Troje, ), obsessive compulsive disorders (Kim et al, ). BM processing is also impaired in individuals with autistic traits (Actis‐Grosso et al, ), and in individuals born preterm who suffer congenital brain lesions (Pavlova et al, ; Taylor et al, ; for review see Pavlova and Krägeloh‐Mann, ). Individuals with ASD have also been reported to be impaired on facial BM processing (O'Brien et al, ).…”
Section: Body Motion and Body Language Readingmentioning
confidence: 99%
“…Higher endogenous oxytocin, a neuropeptide that facilitates social abilities, is associated with better accuracy for anger stimuli and total accuracy in females with schizophrenia, whereas healthy males with higher oxytocin had higher happiness, neutral, and total score accuracy and poorer sadness accuracy (Strauss et al, ). Recent findings from a study in a large cohort of participants showed 1) that patients with schizophrenia were impaired on body‐language reading (point‐light BM emotional expressions of happiness, sadness, anger, fearfulness, and neutral BM) compared with TD individuals and 2) that happiness and lack of emotions were easier to recognize (Vaskinn et al, ; see also Actis‐Grosso et al, ). However, gender effects were not found in body language reading.…”
Section: Body Motion and Body Language Readingmentioning
confidence: 99%
“…For instance, children with ASD showed early difficulties in orienting toward BM (Klin and Jones, 2008;Klin et al, 2009) and no preference for biological over scrambled motion (Blake et al, 2003;Annaz et al, 2012). Moreover, difficulties in recognizing emotional BM has been consistently reported in children (Moore et al, 1997;Fridensonhayo et al, 2016), adolescents (Hubert et al, 2007;Parron et al, 2008) and adults with ASD (Atkinson, 2009;Philip et al, 2010;Nackaerts et al, 2012;Alaerts et al, 2014) or with high autistic traits (Actis-Grosso et al, 2015). However, other studies failed to find differences between neurotypical individuals and people with ASD when emotionally neutral movements were presented (Moore et al, 1997;Hubert et al, 2007;Parron et al, 2008;Murphy et al, 2009;Saygin et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Another benefit of body language reading is that, although verbal information flow is believed to be easily kept under control, body movement often reveals our true feelings and dispositions. Typically developing (TD) individuals are proficient in inferring emotions and intentions of others represented by biological motion (BM) in point-light displays minimizing the availability of other cues (such as body shape or outfit) and, thereby, isolating information conveyed by BM solely (Figure 1) (e.g., Dittrich et al, 1996;Pollick et al, 2001;Atkinson et al, 2004;Heberlein et al, 2004;Clarke et al, 2005;Manera et al, 2010;Alaerts et al, 2011;Sokolov et al, 2011;Krüger et al, 2013;Actis-Grosso et al, 2015;Vaskinn et al, 2016). Perceivers can judge emotional content of dance, represented by a few moving dots located on a dancer's body, with anger being the most reliably identified emotion (Dittrich et al, 1996).…”
Section: Introductionmentioning
confidence: 99%